The Effect of Working Capital Management and Financial Performance of Banks: A Case Study of Centenary Bank, Mukono Branch - Harriet Muwugumya (Uganda Christian University, 2025)
The study demonstrated how working capital management affects banks' financial performance using Centenary Bank’s Mukono branch as a case study. In particular, it looked at the relationship between bank financial performance and accounts receivable management, established the relationship between bank financial performance and accounts payable management, and evaluated the relationship between bank financial performance and cash management. A cross-sectional survey research design was employed to conduct the study, and both quantitative and qualitative research methods were applied. During the data gathering process, both purposive and basic random sample techniques were applied, along with questionnaires and interviews. Despite 44 responses, the study additionally used a sample size of 48 respondents who are managers and staff within the study setting. The results of the study demonstrated how important good financial management techniques are to improving banks’ financial performance. More financial strength and profitability are mostly a result of efficient cash management, accounts payable management, and accounts receivable management. Effective accounts receivable functions maximize cash inflow and minimize credit risks, while effective accounts payable management improves liquidity and operational efficiency. Additionally, effective cash management practices like maximum balance maintenance, forecasting, and the use of sophisticated technology are critical to overall financial success. Collectively, they indicate their strong impact on the financial performance of banks, and they confirm the relevance of these practices for lasting financial well-being and stability. Finally, the study proposed the need for improved accounts receivable management practices in Centenary Bank, Mukono branch. The study also proposes the need for enhanced accounts payable management policies and the need for stringent cash management practices to enhance financial performance. Lastly, the study proposed the need for continuous training and development of staff members handling working capital management.
Undergraduate